(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
The article describes the creative process behind Elefanteatro, a street parade featuring a giant puppet that narrates the saga of a migrant family in search of a better life. Themes of immigration and sustainability are embedded in the diegesis of the performance, led by puppet theater group Pigmalião Escultura que Mexe in musical collaboration with Grupo Oriundo de Teatro. Engaging with concepts akin to “bare life” and “precarious life”, as proposed by Giorgio Agamben and Judith Butler, respectively, the work aligns with the political commitment of artistic representation to activate new perceptions and provoke ruptures in times marked by cruelty and intolerance.